Policy Analysis of the Japanese Academic Evaluation System - Zhou, Chunjuan; Deng, Lei (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: This study thoroughly analyzes the 2017 revision of the Japanese "Ministry of Education, Culture, Sports, Science and Technology (MEXT) Guidelines for Research and Development Evaluation", exploring its response to the evolving demands of society and technology, and enhancing the scientific and practical aspects of the research evaluation system. The aim is to deeply understand the policy objectives of the evaluation system and its actual implementation in scientific practices. Materials and Methods: Utilizing document analysis and comparative methods, this research revisits the historical development of Japan's academic evaluation system, particularly focusing on the 2002 and 2017 editions of the guidelines. Moreover, through comparative analysis, the evolution between these versions and their effectiveness in practical applications are assessed. Results: The 2017 edition of the guidelines emphasizes a problem-oriented approach, focusing more on aligning research with societal needs. Enhancing the transparency and public visibility of the evaluation processes effectively boosts the social value and economic impact of research activities. This edition also specifically supports young researchers by reducing their evaluative burdens and providing a more favorable environment for their scientific careers. Conclusion: (1) The 2017 edition of the guidelines shifts the focus of the evaluation system towards addressing actual social and technological challenges, enhancing the societal value and economic impact of technological innovations. It also improves the credibility of research activities and public support for scientific funding. (2) In its implementation, Japan has introduced more detailed evaluation standards and a diversity of evaluative bodies, enhancing the comprehensiveness and objectivity of the evaluations. This has led to increased job satisfaction among researchers and sustained research activities. Overall, the implementation of the 2017 guidelines has significantly improved the efficiency and effectiveness of Japan's academic evaluation system.